PENGUATAN MODAL MANUSIA DAN PENINGKATAN LITERASI EKOLOGI MELALUI PEDAGOGI SPESIFIK MATERI:PENGEMBANGAN MODEL DALAM PEMBELAJARAN EKOLOGI MELALUI PENELITIAN EKOFISIOLOGI TIKUS SAWAH - Puguh Karyanto; Baskoro Adi Prayitno; Sajidan Sajidan; Suwarno Suwarno (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Education for sustainable development emphasizes on the effectiveness of diffusion of environmentally friendly knowledge and skill to people to have positively environmental attitude in the human-environment interface. In scholarly activities, such transfer of knowledge and value involves particular strategy of transfer ensuring that the given knowledge has impacted on the affective and action. Indeed, theories in environmental psychology suggest that appropriate education changes people’s environmental attitude and behavior.  Theories, approaches, strategy and models of learning are available and can be scrutinized to provide the best way in teaching of ecology in particular concept. Here, the eco-physiological research towards rice-field rats is used as the learning material. Borg and Gall method of research and development can also be used guiding the methodological steps in this review. Keywords : human capital, ecological literacy, subject specific paedagogy, ecophysiological research